Are Measures of Physical Function of the Neck Region Associated With Poor Prognosis Following a Whiplash Trauma?: A Systematic Review. Issue 3 (24th March 2022) - Alalawi, Ahmed; Mazaheri, Masood; Gallina, Alessio; Luque-Suarez, Alejandro; Sterling, Michele; Falla, Deborah
Abstract : Objective: The objective of this study was to synthesize the current evidence regarding the predictive ability of measures of physical function (PF) of the neck region and perceived PF on prognosis following a whiplash injury. Materials and Methods: Electronic databases were searched by 2 independent reviewers up to July 2020, including MEDLINE, EMBASE, CINAHL, PsycINFO, Scopus, and Web of Science as well as gray literature. Eligible studies were selected by 2 reviewers who then extracted and assessed the quality of evidence. Observational cohort studies were included if they involved participants with acute whiplash-associated disorders (WAD), followed for at least 3 months postinjury, and included objective measures of neck PF or self-reported measures of PF as prognostic factors. Data could not be pooled and therefore were synthesized qualitatively. Results: Fourteen studies (13 cohorts) were included in this review. Low to very low quality of evidence indicated that initial higher pain-related disability and higher WAD grade were associated with poor outcome, while there was inconclusive evidence that neck range of motion, joint position error, activity of the superficial neck muscles, muscle strength/endurance, and perceived functional capacity are not predictive of outcome. The predictive ability of more contemporary measures of neck PF such as the smoothness of neck movement, variability of neck motion, and coactivation of neck muscles have not been assessed. Discussion: Although initial higher pain-related disability and higher WAD grade are associated with poor outcome, there is little evidence available investigating the role of neck PF on prognosis following a whiplash injury.